1993
DOI: 10.1111/j.1525-1594.1993.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Terumo Capiox Centrifugal Pump and Its Clinical Application to Open Heart Surgery: A Comparative Study with the Roller Pump

Abstract: We have developed the Terumo Capiox centrifugal pump (CXP), which consists of a rotor having a unique straight-path design to reduce pump rotational speed without decreasing hydraulic efficiency. The CXP was tested in vitro for blood trauma with a specially designed test circuit using fresh bovine blood. The Biopump (BP) (Medtronic, Minneapolis, MN. U.S.A.) and the roller pump (RP) were used as controls. The CXP demonstrated the smallest elevation of free plasma hemoglobin cornpared with the BP and the RP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 1 publication
3
6
1
Order By: Relevance
“…These results were also confirmed in a small nonrandomized study by Nishida et al. (21). However, other nonrandomized clinical trials did not observe a significant platelet count difference between the RP and CP after 120 min (20,22,23).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…These results were also confirmed in a small nonrandomized study by Nishida et al. (21). However, other nonrandomized clinical trials did not observe a significant platelet count difference between the RP and CP after 120 min (20,22,23).…”
Section: Discussionsupporting
confidence: 63%
“…Proponents of CP technology espouse the improved blood handling characteristics of the pump compared to a RP (1,2,21,27). However, our metaanalysis did not demonstrate any difference between pump type and platelet count, PFH, and WBCs at the ECP and PDO.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The CAPIOX SP Pump (SP pump, Terumo Corporation, Tokyo, Japan) is widely used for ECMO or open heart surgery , but this pump also has the risk of thrombus formation around the bearing after long‐term use for several days . In order to overcome this problem, a novel centrifugal pump, the CAPIOX SL Pump (SL pump, Terumo Corporation), was developed.…”
mentioning
confidence: 99%
“…Some studies have shown that for applications in the extracorporeal circulation when high pressures and low flows are required, the roller pumps show better hemolyses indexes than the centrifugal pumps [3]. Thus, a number of modifications in the "design" have been researched extending its application and augmenting its efficiency in high pressures and low flow conditions [4][5][6].…”
Section: Fig 1 -Prototypes Of the Blood Pump And The Modifications Imentioning
confidence: 99%